HIGHER-ORDER THINKING SKILLS ON TEACHERS-MADE TESTS BY ENGLISH TEACHERS OF A SENIOR HIGH SCHOOL IN BENGKULU CITY - Serla Apriana; Azhar Aziz Lubis; Dedi Sofyan (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2022)
The objectives of this study are to investigate the composition of Higher Order Thinking Skills (HOTS) on the English teacher-made test based on the revised Bloom’s taxonomy and investigating the quality of the teacher-made tests viewed from the composition of HOTS. This study was a content analysis that used a triangulation design: data transformation model mixed method approach. The data of this study were teacher-made test sets that consisted of 136 questions. The data were analyzed by understanding the operational verbs used in each item of the teacher-made test based on the cognitive domain of revised Bloom’s taxonomy. Then, data were put in a checklist table based in each cognitive domain category. After that, the data were calculated quantitatively and interpreted qualitatively. The results show that the composition of HOTS was lower than the Lower Order Thinking Skills (LOTS) of all questions on the teacher-made tests. The most frequent cognitive domain of the Bloom’s taxonomy found on the teacher-made test was C2 (Understand), followed by C4 (Analyze), C3 (Apply), C1 (Remember), C5 (Evaluate), and C6 (Create). Moreover, the quality of the teacher-made tests viewed from the composition of HOTS was in a less proportional criterion. In conclusion, the findings indicate constructing a test based on the principles of HOTS seem still problematic for Senior High School English teachers.